User involvement, training and education of the user, formalization of the development of information system and support of top management to the performance of Udayana University accounting information systems: organizational commitments as moderate variable - Diansari, Luh Mastri; Sujana, I Ketut; Budiasih, I Gusti Ayu Nyoman; Sari, María M. Ratna (International research journal of management, IT and social sciences, 2020)
The purpose of this research is to find out and analyze the influence of user involvement, user training and education, formalization of information systems development, and top management support to the performance of accounting information systems at Udayana University with organizational commitment as moderating. Udayana University has developed and applied information systems, one of the breakthroughs in strengthening information technology is the construction of a system called the Accounting and Financial Information System (SIAKU). With the application of SIAKU, it shows a high commitment from Udayana University, to implement good financial governance, through the accountability and transparency offered from this system. This study uses a sampling method saturated with respondents who are all Treasurers Spending Assistant and Member Treasurer Spending Assistant Work Unit of Udayana University. Data analysis techniques used are multiple linear regression analysis and moderation regression analysis (MRA). The results showed that User Involvement, User Training, and Education, Formalization of Information Systems Development, Top Management Support had a positive effect on Accounting Information System Performance and Organizational Commitment could moderate these positive influences.